Developing a Comprehensive, Interdisciplinary Concussion Program. (July 2020) - Chen, Jamie; Kouts, Jill; Rippee, Michael A.; Lauer, Stephen; Smith, David; McDonald, Tracy; Kurylo, Monica; Filardi, Tanya
There has been a growing trend of local and national coverage of and interest in concussion injuries over the past 2 decades. Increasing public concern over potential catastrophic and unknown long-term effects of sports-related concussion injuries has led to an acknowledgment of the strong public health need for addressing all concussion injuries, regardless of mechanism of injury. In efforts to address this need for concussion prevention and management, both in sports and nonsports, The University of Kansas Health System initiated the interdisciplinary Center for Concussion Management program in 2012. The program was created as a virtual clinic concept and includes voluntary participation from various providers across the institution, limited budget, and space obstacles. Since its inception, the program has continued to operate as its initial design of a multidisciplinary team model outside the sole ownership of 1 department, and has expanded to include education and outreach to local and regional schools and groups.